The Mediating Role of an Extraversion Personality in the Relationship Between Language Learning Motivation and the Communicative Competence of Students - Echavez, Darlin; Oliva, Elleine Rose A. (Journal of Natural Language and Linguistics, 2025)
This study aimed to determine the mediating role of an extraversion personality in the relationship between language learning motivation and communicative competence in the Filipino subject among Grade 10 students in public schools in Sta. Maria, Davao Occidental. A non-experimental descriptive-correlation design was employed in the research. Data were collected from 400 students using three questionnaires as research instruments. Findings revealed that the levels of Language Learning Motivation and Communicative Competence were very high, while Extraversion Personality was high. There was also a significant relationship between language learning motivation and extraversion personality, language learning motivation and communicative competence, and between language learning motivation and communicative competence. Moreover, it was discovered that extraversion personality partially mediated the relationship between language learning motivation and communicative competence. Thus, teachers are encouraged to consider students’ communicative competence in senior high school by fostering meaningful language learning motivation and promoting extraversion personality traits.